ANALISA SUDUT PERSIMPANGAN DAN INDEKS BIAS PADA MACH ZEHNDER INTERFEROMETER OPTIK DENGAN MENGGUNAKAN PROGRAM ELEKTROMAGNETIK CST - Nurul Huda; Dadin Mahmudin; Lilik Hasanah; Yusuf Nur Wijayanto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
In the research has been done the design of a component environment sensor based waveguide Mach Zehnder Interferometer (MZI). The material used is a polymer type polymide loss free, which varied with SiO2. The design is done by sketching and simulate the structure of MZI in the program Computer Simulation Technology (CST) by varying the analyte in the waveguide so that there will be changes in the refractive index which causes a wavelength shift at Mach Zehnder interferometer output by varying the angle 80 and 100 so as to be detectable change in the refractive index of 1.01;1.1 and 1.2 with a fixed length sensing arm 4 Î¼m. Keywords : CST , Mach Zehnder interferometer , refractive index , waveguide .